“The Fadors Influence Consumer’s Acceptance towards High Speed Broadband by Telekom Malaysia Berhad Kota Bharu Kelantan / Suriana Sapie - Sapie, Suriana (Faculty of Business and Management, 2008)
Modem societies today are very selective in choosing best communications medium or technology for themselves in order to make them more advanced than others.. At the same time they totally follow the technological advancement especially in telecommunications industry. Due to that the researcher conducted this study to identify factors that influence consumer's acceptance towards High Speed Broadband by TM. The factors which are the independent variable are perceived usefulness, awareness and price. Dependent variable is consumer's acceptance towards High Speed Broadband by TM. The objective of this study is to examine impact of each independent variable to its dependent variable as well as to conclude the relationships exist. The researcher used descriptive research design as it attempts to determine perceptions of product or service characteristics. At the same time it also determines the degree to which variables are associated. In collecting the data, the researcher obtains from primary from questionnaires, while secondary data collected from journals, articles, books, reports and internet. Convenience sampling was used for this study as it allows obtaining a sample of convenient elements as well as accessible, easy to measure and cooperative. Due to that 120 respondents selected randomly to answer questionnaires which the researcher focused on TM point customers, Telekom employees itself and public at shopping mall. Then the researcher analyzed the data from questionnaires using Statistical Package for Social Science 14.0 Students Version. Data was interpreted and test using frequency distribution analysis. Correlation analysis and simple regression used to test hypotheses. The results show that all three independent variables have positive relationships with dependent variables. In terms of hypotheses testing, all three hypotheses rejected null hypotheses. In fact, other factors may exist such as cost, trend, mobility and value added services. Recommendations outline by the researcher are to focus on competitive advantage like such as focus on offering various service packages to subscribers. Furthermore promotions should be done aggressively and at the same time make service improvement like mobilize and value added services. The researcher lastly hope that further research will be done as it is meaningful to outline the hidden issues and factors that need to be focused by High Speed Broadband provider.